Penerapan V-Model dalam pengembangan sistem penerimaan siswa baru Menggunakan PHP dan mySQL - Jayaun; Dedi Supriyadi (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
The rapid development of technology and communication requires humans to act faster with attention to efficiency and effectiveness. SDIT Insan Kamil as an institution engaged in the field of Education. The expected goal of this research is to build a P2DB information system that is used to store and utilize new student registrations owned by SDIT Insan Kamil, making it easier to find solutions to the problems at hand. For the data collection method, the researcher did by direct observation. New student enrollment is done by knowledge creation, knowledge sharing and knowledge application. System development method with the V-Model method. The result of this research is to show that the application of new student registration is the solution to the problem.